NONLINEAR STATIC ANALYSIS FOR SEISMIC EVALUATION OF REINFORCED CONCRETE (RC) STRUCTURES USING SEISMOSTRUCT - HAMZAH, HAZMATUL FARHA (2013)
Earthquake is known as the unpredictable disaster that occurs from beneath the earth as a result of a sudden release of energy in the Earth's crust. The impact of this massive disaster is visualized as the shaking ofthe area and caused extensive damages to humankind and environment. Buildings and other structures face extensive damages and collapse due to high earthquake intensity. The response of this structure is becoming the main interest to the structural engineers and researchers to study the structure's behavior under seismic action. Over the past fifty years, there is remarkable progress in this area where the studies concern in understanding the response of structures under seismic loading. Since reinforced concrete (RC) structures are unlike steel materials and heterogeneous, there is still lacking information of response ofRC structures.